#Smartphone Communities. Issue 2 (26th September 2018) - Unterstell, Rembert
Abstract: WhatsApp, Snapchat and Pokémon GO: Konstanz‐based media researcher and Heinz Maier‐Leibnitz Prize recipient Isabell Otto is studying modern digital media from a cultural studies perspective / Media and participation between demand and entitlement